Connected epistemic practices in laboratory‐based engineering design projects for large‐course instruction - Koretsky, Milo D.; Nefcy, Erick J.; Nolen, Susan Bobbit; Champagne, Audrey B. (Science education (Salem, Mass.), 2023)
In both K‐12 and university settings, instructors and curriculum developers need to create learning experiences that provide students opportunities to engage in the disciplinary practices of science and engineering. However, instructional contexts pose challenges in developing such tasks. Using a framework focusing on conceptual and material epistemic practices and tools, we used a within‐subjects comparison to explore two different types of task designs, given realistic constraints posed by a large‐enrollment university engineering laboratory course. We investigated students’ modeling and experimental activity at scale using an innovative data analysis tool, Model Maps, looking for evidence of epistemic practices in student laboratory notebooks and in their post‐project presentations. We compared inscriptions of 29 teams across three laboratory projects and found a greater number and diversity of model components in a virtual laboratory project than in two physical laboratory projects. While fitting into the same instructional “space,” the virtual laboratory task, compared to the physical tasks, better afforded iteration. The iterative development engaged students in two important features of engineering epistemic practice. First, teams had the opportunity to engage in interlocking conceptual and material practices. Second the need to reconcile experimental data with their process models elicited the authorship of free moves together with the accountability of forced moves. Implications for designing instruction to incorporate epistemic practices in engineering and science education are described.